A modified Papanicolaou Society of Cytopathology system for reporting respiratory cytology specimens: Implications for estimates of malignancy risk and diagnostic accuracy. Issue 11 (28th July 2021) - Layfield, Lester J.; Esebua, Magda
Abstract: Background: In 2016, the Papanicolaou Society of Cytopathology (PSC) proposed a classification scheme for reporting cytologic specimens obtained from the respiratory system. Diagnostic sensitivity, specificity, and risk of malignancy were reported for endobronchial ultrasound guided fine needle aspiration but data for other sampling techniques has been poorly documented. Methods: In 2016, a modified version of the PSC guidelines was adopted at the University of Missouri for classification of sputum, bronchial washing, bronchial brushing, and fine‐needle aspiration specimens. Specimens assigned to the negative category included all specimens containing evaluatable inflammatory or epithelial cells including benign appearing respiratory epithelium. Only specimens with marked artifactual distortion or obscuring blood or mucus were placed in the non‐diagnostic category. Results: 672 bronchial washing specimens (479 with histology) and 511 bronchial brushings specimens (324 with histology) were reviewed. Washing specimens were classified as non‐diagnostic (3%), benign (73%), atypical (10%), suspicious (4%), and malignant (10%). Bronchial brushing specimens were classified non‐diagnostic (0.4%) benign (73%), atypical (6%), suspicious (3%), and malignant (17%). Malignancy risks for bronchial washings were insufficient (50%), benign (38%), atypical (62%), suspicious (83%), and malignant (98%). Risks of malignancy for bronchial brushings were insufficient (0%), benign (32%), atypical (79%), suspicious (75%), and malignant (94%). Conclusion: Malignancy risks associated with bronchial washings and bronchial brushings are different than those reported for EBUS FNA. When the benign category includes specimens with "normal" appearing cellular elements, the risk of malignancy is substantial (between 32% and 38%).